Modelling and experimental measurements of the mechanical response of piezoelectric structures from millimetre to micrometre. (4th July 2018) - Bavencoffe, M.; Tembhurnikar, N.; Negulescu, B.; Wolfman, J.; Feuillard, G.
ABSTRACT: Laser interferometry techniques have shown their ability to assess the mechanical response of a piezoelectric thin film. To support these investigations, a numerical study based on the finite element method is carried out: three-dimensional modelling of piezoelectric samples from bulk materials to thin films is examined. For each considered sample, a time-dependent analysis and a frequency domain study are performed. By performing time-dependent analysis, we obtain effective piezoelectric coefficient, d 33, of the samples. The frequency domain study helps to calculate the frequency response of these samples. The calculated d33 values and the first frequency resonance values are then compared with the experimental data.